A Study on The Seventh-Grade Teaching Speaking Methods at MTs Muhammadiyah Malang - Nisa Wati; Rina Setyaningrum (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show